1998
DOI: 10.1152/ajplung.1998.275.2.l330
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of fibronectin expression in rat lung by ozone and an inflammatory stimulus

Abstract: This study investigated the relationship of fibronectin expression and induction of pulmonary inflammation by ozone (O3). Rats were exposed to 0.8 parts/million O3 to induce lung inflammation. A second inflammatory stimulus, rabbit serum, was applied intratracheally to augment O3-induced inflammation. Bronchoalveolar lavage fluid (BALF) and lung tissues were analyzed for fibronectin protein and mRNA expression. Blood plasma was analyzed to investigate the potential of a minimally invasive procedure in predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Non significant increase in nucleic acids contents was observed at the lowest ozone exposure times (0-40 min) ( Table 3). The obtained result was in accordance with Gupta et al (2010) who stated that there are a significant increases in the levels of protein, RNA following ozone exposure. Also Poli et al (2007) found that with longer duration of ozone exposure (up to 30 min) cell viability decreased and membrane permeability was compromised as indicated by more significant increase in protein and nucleic acid leakage and lipid oxidation.…”
Section: Lipid and Tryptophan Oxidation Of F Oxysporiumsupporting
confidence: 91%
“…Non significant increase in nucleic acids contents was observed at the lowest ozone exposure times (0-40 min) ( Table 3). The obtained result was in accordance with Gupta et al (2010) who stated that there are a significant increases in the levels of protein, RNA following ozone exposure. Also Poli et al (2007) found that with longer duration of ozone exposure (up to 30 min) cell viability decreased and membrane permeability was compromised as indicated by more significant increase in protein and nucleic acid leakage and lipid oxidation.…”
Section: Lipid and Tryptophan Oxidation Of F Oxysporiumsupporting
confidence: 91%
“…Therefore, Fn may act as a bridge between M. tuberculosis and the AM. As Fn is a constitutively expressed protein in the lung (7) and is increased during inflammation (16), this interaction may represent a normal host response in the initial week of new infection in the alveolar spaces.…”
Section: Discussionmentioning
confidence: 99%